Prospects of using low-grade fuels of Tomsk region for thermal technology use - R. B. Tabakaev; A. V. Kazakov; A. S. Zavorin (Известия Томского политехнического университета: Инжиниринг георесурсов, 2009)
The relevance of the work is conditioned by the necessity of including renewable energy sources, in particular biomass, into fuel and energy balance. The aim of the paper is the experimental testing of heat technologies in producing fuel briquettes in various types of low-grade fuels of Tomsk region. Using the physical experiment method the authors tested the largest manifestation of low-grade fuels of Tomsk region for suitability of their processing into fuel briquettes. Thermotechnical characteristics of low-grade fuels of Tomsk region, the material balances of their thermal technological processing, the results of forming fuel briquettes were determined through the research. Thermotechnical and strength characteristics of the briquettes allow making the following conclusions: the developed thermal technology should be used for processing wood chips and Kandinsky peat; processing of brown coal of Talovsky deposit and peat of Sukhoi deposit is possible at detailed feasibility study; Karasevsky sapropel and Arkadevsky peat as source raw material for thermal technology are least suitable because of very high ash value of the produced fuel briquettes.